2013
DOI: 10.1063/1.4824800
|View full text |Cite
|
Sign up to set email alerts
|

Foundations of ab initio simulations of electric charges and fields at semiconductor surfaces within slab models

Abstract: Semiconductor surfaces were divided into charge categories, i.e. surface acceptor, donor and neutral ones that are suitable for simulations of their properties within a slab model. The potential profiles, close to the charged surface states, accounting for explicit dependence of the point defects energy, were obtained. A termination charge slab model was formulated and analyzed proving that two control parameters of slab simulations exist: the slope and curvature of electric potential profiles which can be tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 41 publications
3
35
0
Order By: Relevance
“…In the recent study we have shown how the adsorption energy depends on the electric charge transfer between solid bulk or the existing surface states and the new states emerging due to the presence of the adsorbate. 5,6 It was shown that in the absence of the charge transfer the adsorption energy attains the value determined by the energy of the bonding. The novel recently introduced idea is the energy dependence on the electronic charge transfer.…”
Section: The Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the recent study we have shown how the adsorption energy depends on the electric charge transfer between solid bulk or the existing surface states and the new states emerging due to the presence of the adsorbate. 5,6 It was shown that in the absence of the charge transfer the adsorption energy attains the value determined by the energy of the bonding. The novel recently introduced idea is the energy dependence on the electronic charge transfer.…”
Section: The Resultsmentioning
confidence: 99%
“…The novel recently introduced idea is the energy dependence on the electronic charge transfer. 5,6 The new phenomenon originates from the fact that the exchange of the electron between the Fermi level and the emerging surface state of different energies generates an additional energy gain. The energy difference of these two states may reach several electronvolts, affecting the adsorption energy considerably.…”
Section: The Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first-principles simulation of doped semiconductor surfaces has been addressed in recent literature using different approaches. Krukowski, Kempisty, and co-workers have manipulated the location or charge of passivating, back-side atoms to reproduce the effects of the SCR on the electronic structure of finite slab simulations of charged surfaces [19][20][21]. Using this, they demonstrated that the electric field of the SCR may shift surface state energies, a phenomenon that they termed the "surface-state Stark effect."…”
Section: Introductionmentioning
confidence: 99%